SOSIALISASI PEMANFAATAN TANAMAN KELOR UNTUK KESEHATAN KELUARGA BAGI GURU MTS ARIFAH GOWA - GH, Muliana; Patongai, Dian Dwi Putri Ulan Sari; Suryani, Andi Irma; Adminira, Zuhrah; Sadriani, Andi (Ininnawa : Jurnal Pengabdian Masyarakat, 2024)
The Moringa plant (Moringa oleifera) is known as the "miracle tree" due to its exceptional nutritional content and various health benefits. However, knowledge and utilization of this plant remain limited, especially among educators. This research aims to promote the use of Moringa as an alternative for improving family health to teachers at MTs Arifah, Gowa. The method used includes a socialization process consisting of lectures and interactive discussions. This activity is expected to enhance the teachers' knowledge and skills in using Moringa not only as a health supplement but also in everyday food preparation. The results of the activity showed a significant increase in teachers' knowledge and interest in the various uses of Moringa. This socialization effort has the potential not only to improve the nutritional and health status of teachers and their families but also to equip them with the tools to educate students about the importance of nutrition and the use of local resources for health. Keywords: Moringa plant, family health, socialization, MTs Arifah Gowa